Knowledge and experience of lean thinking amongst senior health care managers in selected South African public hospitals - Logandran Naidoo; Ziska Fields (SPOUDAI - Journal of Economics and Business, 2019)
With the pressing need for quality improvement and with a view to adopting Lean as a systematic management approach in a crisis-ridden health care sector in South Africa, it was an opportune time to investigate the baseline level of knowledge and experience of Lean amongst senior health care managers in public hospitals in KwaZulu-Natal (KZN), South Africa. The research was centered on a positivist paradigm (involving quantitative methods) and took the form of an observational, descriptive study in KZN. This article presents the results of one of several key objectives of a seminal PhD study conducted in KZN. A total of 218 senior managers located in 73 hospitals participated in the research. A self-administered, semi-structured questionnaire was used. Most managers indicated that they have not heard of Lean before and had no prior practical experience thereof. All participants indicated that they were interested in learning more about Lean, that there was an opportunity for adopting Lean practices and that Lean could possibly improve the operational performance in their hospitals.
Keywords: I19; L23; M19; 330; Lean knowledge; Lean thinking; Lean in public hospitals; Experience with Lean; Operations management